Georgetown Eye Health Initiative - Elyse Linson; Tatiana Zanganeh; Michael Korchak; Jay Lustbader (Journal of Student-Run Clinics, 2016)
As diseases that affect vision become increasingly prevalent, access to vision screenings will become more important. The inhabitants of D.C. General Family Shelter, a homeless shelter in Southeast Washington, D.C., have limited access to primary care, let alone vision care. Educational strategies to improve this disparity provide students the opportunity to develop the attitudes, knowledge, and skills necessary for providing a needed service for underserved patients. Medical students, resident physicians, and faculty of Georgetown University School of Medicine, MedStar Georgetown University Hospital, and MedStar Washington Hospital Center created the Georgetown Eye Health Initiative (GEHI) to provide an opportunity for students to participate in vision and eye health screening clinics for the underserved and homeless. The establishment, missions, and protocol of GEHI as a functional and educational clinic are described, as well as challenges encountered and future directions. Medical students, residents, and faculty working in collaboration can provide increased access to vision screening and eye health education for the medically underserved. With a focus on community engagement and education, ophthalmology represents a specialty area that has been previously overlooked in student-run clinics and has a significant role at the forefront of preventative care.